Applications of Nanotechnology in Food Processing, Packaging and Food Safety Risks - Yohanes Alan Sarsita Putra; Victoria Kristina Ananingsih; S.E.A Setiawan (Turkish Journal of Agriculture: Food Science and Technology)
While nanotechnology is widely applied in diverse fields like agriculture, biochemistry, and medicine, it remains a rapidly advancing discipline that introduces more complex applications in food systems compared to traditional technologies. The rapid advancement of nanotechnology has brought significant changes to multiple aspects of food science, including processing, packaging, storage, transportation, functionality, and safety. Various nanostructured materials, ranging from inorganic metals, metal oxides, and their composites to bioactive agents incorporated into organic nanoparticles, have been employed within the food industry. Regardless of the substantial advantages of nanotechnology, there are growing concerns about its use, mainly related to the potential accumulation of nanostructured materials in the human body and the environment, leading to various health and safety risks. Therefore, it is crucial to consider safety and health concerns and adhere to regulatory policies while manufacturing, processing, intelligent packaging, and consuming nano-enhanced food products. This review aims to provide a fundamental understanding of nanotechnology applications in food packaging and processing industries while identifying prospects and potential risks associated with nanostructured materials. Additionally, it delves into the health, risk, and hazard aspects of nanoparticles in food and their role in food safety assessments, highlighting specific areas of concern.